(3EOGQI GdLhOI GdTGedI (BTQM (3hGdCjRh (BISO s - (3MejO YHO GdfHj(B, (3GdWGFjs; (3QVG UGMH Bd Ydj(B, s ((3YeGf(B:s (3eDSSI GdhQGb(B,s, 2003)
(3EOGQI GdLhOI GdTGedI,Gdeaghe hGdJWhQ GdJGQjNj,EOGQI GdLhOI GdTGedI GdfXGe(B-(3GdGjRh (BISO(3,GdGjRh Gdeaghe hGdCgejI hGdNWhGJ GdCSGSjI ddMUhd YdjgG,GdehGUaI GdOhdjI hGdfehPL GdebJQM,GdehGUaI GdOhdjI (BISO9000 (3GdGUOGQ GdKGdK (B2000(3,GdfehPL GdebJQM hOdjd GdLhOI ddTQcIs
(3HjHdjhZQGajG U(B.295s
Keywords: (3GdLhOI GdTGedIs; (3GdefXeI GdOhdjI ddJbjjSs; (3VHW GdLhOIs